Key Factors Influencing Distributor Purchase Decisions for NPK Phonska Plus Fertilizer - Saeful Huda Rijaludin; Vita Ratnasari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Nitrogen, Phosphorus, Potassium (NPK) fertilizer production in Indonesia is dominated by private producers and imported products, making PT Pupuk Indonesia's market share for NPK Phonska Plus relatively small. To increase sales and market penetration, companies need to understand distributor preferences as an important part of the supply chain. The study aims to identify purchasing preferences and distributor behavior that have a significant impact on product marketing. This study was conducted by surveying 212 distributors in East Java, which is the largest market for NPK Phonska Plus. Using observation and survey methods, data was processed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach, targeting distributors in non-city areas of East Java. The results of the study provide an in-depth overview of the factors that influence distributor decisions, such as product quality, price, and service support. Strategic recommendations are formulated to increase competitiveness, strengthen relationships with distributors, and expand the company's market share. With this data-based marketing strategy, PT Pupuk Indonesia can strengthen its position in the domestic market, especially for its flagship product NPK Phonska Plus, facing the challenges of competition in the fertilizer industry in Indonesia.